ANALISIS DESKRIPTIF PENGAJARAN BAHASA ARAB TERHADAP PENINGKATAN MUTU PENGKAJIAN AYAT-AYAT AHKAM DI JURUSAN SYARIâAH STAIN PAREPARE - YUNUS, H. MUKHTAR (Kuriositas: Media Komunikasi Sosial dan Keagamaan, 2014)
Implementation of the Arabic language teaching has been in the Department of Islamic Satate college (STAIN) Parepare refers to the same system applied in various colleges religions. With reference to the curriculum, syllabus and the value of credits that have been set and the things associated with it is therefore necessary to the preparation of a new curriculum that adapts to the needs of students, especially students need to be material interpretation of verses Ahkam.Factors supporting the Arabic language teaching in improving the quality assessment of the verses of Ahkamof Syariâah Department, the high interest of the students in the study and development programe of Arabic. However, there are several factors that hinder the teaching of the studentâs ability in Arabic, especially students from public schools and the ability of the students are not uniform.There needs to be improvement and improvement in learning Arabic in STAIN Parepare, in order to realize the effectiveness of the reconstruction effort of learning the Arabic language, especially in the Department of Syariâah, be it related to the media and means of learning, professionalism and personality lecturer. Even with the curriculum and syllabus in order to get better results again.